A New Measure of the Financial Cycle: Application to the Czech Republic. Issue 4 (3rd July 2016) - Plašil, Miroslav; Seidler, Jakub; Hlaváč, Petr
Abstract : The recent financial crisis has demonstrated the importance of the linkages between the financial sector and the real economy. This article proposes a suitable and easy-to-apply method for assessing the position of the economy in the financial cycle in order to identify emerging imbalances in a timely manner. The method utilizes a composite indicator, constructed by the authors, that combines variables representing risk perceptions in the financial sector and their reinforcing interactions over the financial cycle. The indicator is calibrated to capture the future credit losses of the Czech banking sector. This method can be used by policymakers for a wide range of policy decisions, including the setting of a countercyclical capital buffer.